Gastrointestinal and Liver Manifestation of Covid-19 - Chikodili Crystal Umejiaku (Clinical Manifestations of Covid-19: A Multi-Disciplinary Approach, 2024)
COVID-19 is caused by a respiratory virus and infected millions of people worldwide leading to a pandemic. Its origin was linked to seafood and wet animal markets therefore the likelihood of having gastrointestinal and liver manifestations is high. GI symptoms are common and mostly self-limiting but where they occur in combination or as a marked symptom, it tends to portend a worse outcome.